2013
DOI: 10.1080/07399332.2013.815751
|View full text |Cite
|
Sign up to set email alerts
|

Women's Preference for Traditional Birth Attendants and Modern Health Care Practitioners in Akpabuyo Community of Cross River State, Nigeria

Abstract: The proportion of women who patronized traditional birth attendants (TBAs) or modern health care practitioners (MHCPs) was compared, including reasons for their choices. A comparative design was adopted to study 300 respondents selected through a multistage systematic random sampling technique. The instrument for data collection was a validated 21-item structured questionnaire. We observed that 75 (25%) patronized and 80 (27%) preferred TBAs, and 206 (69%) patronized and 220 (75%) preferred MHCPs, while 19 (6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Following referrals, clients returned to TBAs as they would to a primary health care worker, such that the TBA was responsible for maternal care coordination. Client confidence in the TBA’s ability to provide quality maternal health services has been reported in other studies in Nigeria and Sierra Leone [ 16 , 17 ]. Even in studies where a higher proportion of TBA clients reported that TBAs (16%) have poor medical skills relative to skilled providers (0.5%), the majority (61%) of clients were satisfied with TBA delivery care [ 18 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Following referrals, clients returned to TBAs as they would to a primary health care worker, such that the TBA was responsible for maternal care coordination. Client confidence in the TBA’s ability to provide quality maternal health services has been reported in other studies in Nigeria and Sierra Leone [ 16 , 17 ]. Even in studies where a higher proportion of TBA clients reported that TBAs (16%) have poor medical skills relative to skilled providers (0.5%), the majority (61%) of clients were satisfied with TBA delivery care [ 18 ].…”
Section: Discussionsupporting
confidence: 52%
“…These factors may lead to non-compliance with postnatal care referrals by TBAs. There is near-consensus over the fact that TBAs provide respectful maternal care relative to skilled health providers [ 16 , 17 , 20 , 28 – 30 ]. A synthesis of qualitative evidence from low and income countries reveals that disrespectful maternal care is a barrier to the use of facility-based delivery in many contexts [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the reasons stated, evidence from other studies showed that some women have preference for traditional birth attendants [ 14 , 15 ] or delivery at home [ 16 ]. To take advantage of this perception among the women, it may be worthwhile to develop synergy between trained midwives and traditional birth attendants.…”
Section: Discussionmentioning
confidence: 99%
“…These, coupled with loss of a previous child could discourage women from adequate uptake of MHC. Favorable dispositions to patronage of traditional birth attendants may also be a factor [ 26 ]. Further research is recommended to fully understand the peculiar situation in the sub-region.…”
Section: Discussionmentioning
confidence: 99%